Are the Mathematics Textbooks for Eighth-Grade Meet the Trends in International Mathematics and Science Study (TIMSS) 2019 Mathematics Framework? - Annis Pertiwi; Wahidin Wahidin (Edumatika : Jurnal Riset Pendidikan Matematika, 2020)
Abstract. This study aims to determine the suitability of mathematics textbooks for eighth-grade with Trends in International Mathematics and Science Study (TIMSS) 2019 Mathematics Framework. This research uses a qualitative research method with a descriptive approach and content analysis techniques. The data of this research are the eighth-grade mathematics textbook. In the textbook analysis, the researcher used three textbooks, namely Penerbit Erlangga, Yudhistira, and the Ministry of Education and Culture (Kemendikbud). The analysis carried out was the analysis of the content domain and knowledge domain based on the TIMSS 2019 Mathematics Framework. The content domain contains numbers, algebra, geometry, and data, and probability. While the knowledge domain contains aspects of understanding, application, and reasoning. In the Penerbit Erlangga book, there are only 2 out of 4 pieces of content contained in TIMSS, while the cognitive domain is 2 out of 3 aspects. Yudhistira book 2 of 4 content contained in TIMSS, while the cognitive domain is 1 of 3 aspects. Kemendikbud’s book is 1 of 4 content domains in TIMSS, while the cognitive domain is 1 of 3 aspects. Therefore the three eighth-grade mathematics textbooks as a whole are still not suitable for the TIMSS 2019 Mathematics Framework. Abstrak. Penelitian ini bertujuan menentukan kecocokan buku ajar matematika kelas VIII dengan Trends in International Mathematics and Science Study (TIMSS) 2019 Mathematics Framework. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif dan teknik analisis isi. Data yang dianalisis adalah buku ajar matematika kelas VIII. Dalam analisis buku ajar, peneliti menggunakan tiga buku ajar yaitu terbitan Erlangga, Yudhistira, dan Kementerian Pendidikan dan Kebudayaan (Kemendikbud). Analisis dilakukan terhadap content domain dan knowledge domain berdasarkan TIMSS 2019 Mathematics Framework. Content domain terdiri dari bilangan, aljabar, geometri, dan data dan peluang. Sedangkan knowledge domain terdiri dari aspek pemahaman, penerapan dan penalaran. Dalam buku Erlangga, terdapat dua dari 4 content domain, sedangkan cognitive domain hanya 2 dari 3 aspek. Buku Yudhistira memuat 2 dari 4 content domain dan hnaya 1 dari 3 aspek cognitive domain. Pada buku Kemendikbud hanya terdapat 1 dari 4 content domain dan hanya 1 dari 3 aspek cognitive domain. Jadi, tiga buku ajar matematika kelas VIII tersebut secara keseluruhan belum sesuai dengan TIMSS 2019 Mathematics Framework.